Penerapan Metode VIKOR(VlseKriterijumska Optimizacija I Kompromisno Resenje) Dalam Membeli Smartphone - Yusril Yusuf; Rakhma Sarita (Journal of Information System Research (JOSH), 2021)
The development of information technology is now increasingly sophisticated and continues to develop. Over time, the latest smartphone releases are increasingly being released with various specifications and brands, and have various prices that can be adjusted to the buyer's budget. So many types and various kinds of specifications make buyers confused about buying a smartphone. Each smartphone has different quality and specifications from each brand, of course, making it difficult for buyers to make decisions in choosing a smartphone. From these problems, a Decision Support System was created in buying a smartphone which aims to make buyers choose the right smartphone. Some of the criteria found from the results of observations and interviews include C1 Price, C2 CPU, C3 ROM, C4 Battery, C5 Camera, and C6 RAM. Research using the VIKOR method of calculation obtained results that can be used as a reference in choosing a smartphone. The purpose of making a decision support system for making decisions in buying a smartphone is fulfilled. This system can help buyers provide recommendations when choosing the smartphone they want to buy with accurate results